Effect of SnO2 on material and radiation shielding properties in SiO2-B2O3-Na2O-K2O-ZnO glass system - Hosgor, Zeynep R.; Unluturk, Mete; Gulmez, Sevgul; Anil, Umit Engin; Yazan, Selcuk Bulut; Hosgor, Gamze; Tabar, Emre (ELSEVIER SCI LTD, 2025)
This study aimed to develop and evaluate SnO2-doped borosilicate-based glasses within the SiO2-B2O3-Na2O-K2O-ZnO system for potential applications in gamma radiation shielding. Glasses containing 2.5 %, 5 %, 7.5 %, and 10 % SnO2 were synthesized using the conventional melt-quenching method and labeled as Sn-X, where X indicates the wt% of SnO2. X-ray diffraction (XRD) analysis confirmed that the glasses had a fully amorphous structure. As the SnO2 content increased, there was a notable rise in the density of trigonal BO3 units and the glass transition temperature (Tg). This phenomenon was attributed to the presence of Sn4+ ions, which stabilize non-bridging oxygens (NBOs) and enhance network connectivity. The densities of the glasses were measured using Archimedes' principle, revealing that the molar volume decreased with higher SnO2 content, likely due to the compacting effect of Sn4+ cations. The radiation shielding properties of the glasses were investigated using a 3 x 3 '' NaI(Tl) detector, with results validated by Geant4 simulations and Phy-X/PSD software. Among all samples, Sn-10 exhibited the highest linear attenuation coefficients (LACs) and the lowest values for half-value layer (HVL), mean free path (MFP), and transmission factor (TF). These results indicate that Sn-10 has superior gamma-ray attenuation performance. This study demonstrates that incorporating SnO2 significantly enhances both the structural integrity and radiation shielding efficiency of borosilicate glasses, making them promising candidates for applications in medical, nuclear, and aerospace fields.
Keywords: Tin oxide; Glass system; Characterization; Radiation shielding; Geant4; OPTICAL-PROPERTIES; BORATE GLASSES; GAMMA; PARAMETERS; B2O3; Materials Science